2008
DOI: 10.1007/s10653-008-9215-4
|View full text |Cite
|
Sign up to set email alerts
|

Using urban man-made ponds to reconstruct a 150-year history of air pollution in northwest England

Abstract: A regional pollution history has been reconstructed for the borough of Halton (northwest England) from four urban ponds in north Cheshire and south Merseyside, using environmental analyses of lake sediment stratigraphies. Mineral magnetism, geochemistry and radiometric dating have produced profiles of pollution characteristics dating from the mid-nineteenth century to present day. These pollution profiles reflect the atmospheric deposition of a range of pollutants over 150 years of intensified industry. Distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
5
0
1
Order By: Relevance
“…Many previous studies suggested that iron sulfides are of importance in polluted environments (Dekkers and Schoonen 1994;Cornwell and Morse 1987;Snowball and Torii 1999;Power and Worsley 2009). As discussed above, greigite is existing within the coastal sediments and its concentration is mainly appearing in magnetic remanence parameters (ARM and SIRM) while in the magnetic susceptibility signal magnetite is clearly dominating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies suggested that iron sulfides are of importance in polluted environments (Dekkers and Schoonen 1994;Cornwell and Morse 1987;Snowball and Torii 1999;Power and Worsley 2009). As discussed above, greigite is existing within the coastal sediments and its concentration is mainly appearing in magnetic remanence parameters (ARM and SIRM) while in the magnetic susceptibility signal magnetite is clearly dominating.…”
Section: Discussionmentioning
confidence: 99%
“…While numerous studies concerned the relationship between MS and the development or pollution history using sediments from lakes or man-made ponds (Hu et al 2003;Power and Worsley 2009), the use of magnetic properties from coastal sediments for such purpose has been limited because of multiple influencing factors. Magnetic minerals and their sources must be determined before one can relate magnetic parameters of marine sediments to the development history (Hilton 1987;Yu and Oldfield 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Mapping in this way can produce high-resolution spatial 'databases' of pollution characteristics, identify pollution hot spots and, with the application of postcoded health data, may aid epidemiological investigations into the health effects of vehicle-derived particulates. This work forms part of the ongoing research into the role of urban sediments for spatial and temporal pollution monitoring (Power and Worsley 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Mineral magnetic analysis of urban sediments is increasingly becoming a viable, inexpensive and reliable complimentary diagnostic tool to characterise particulate pollution (Muxworthy et al 2003;Shu et al 2000) and identify temporal (Power and Worsley 2008;Oldfield et al 1983;Dekkers 1997;Worsley et al 2005) and spatial PM trends (Hoffmann et al 1999;Strzyszcz et al 1996). The method is reliable, rapid, non-destructive and sensitive to low detection levels, and yields data on the grain size, behaviour and concentration of magnetic grains within a sample.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sediments from a stormwater retention pond in New York track the usage of leaded gasoline as well as a decline in arsenic deposition after pollution control technologies were implemented at nearby coal-fired power plants 4 . Sediments from urban ponds in northwest England were used to reveal the rise of pollutant deposition from the beginning of the industrial revolution in the nineteenth century, to the decline in the wake of Clean Air Acts in the mid twentieth century 5 . These kinds of reconstructions could be used to inform our understanding of diseases with long latency times.…”
mentioning
confidence: 99%